NURSING EDUCATION ON PHARMACOLOGICAL INTERVENTIONS - Ahmad Asheq M. Abinayesh, Awwad Qahyem Mashaan Alshammary, Ahmad Salem Mutlaq Alkhaldi, Eid Nawaf Hatl Alanazi, Ali Abdoh Ali Alshaikhi, (Chelonian Research Foundation, 2024)
Core drug knowledge also includes pharmacotherapeutics, pharmacokinetics, pharmacodynamics, contraindications and precautions, side effects, and drug interactions. It also includes basic pharmacologic information about each drug. Core patient variables are the traits that make a patient stand out at any particular time. (Maciej Serda et al., 2012) However, in critical care units (ICUs), intensive care nurses are always on hand to supervise the patient's care and keep an eye on their condition. The foundation of contemporary intensive care is interprofessional collaboration. According to Henderson (1966), a nurse's general goal is to assist patients in meeting their basic needs while they are in precarious situations and to aid in their transition to independence.(Harris, Godoy and Nathe, 2014; Larsen, Johannessen and Heggdal, 2022). Drug-related issues, especially the safe transfer of the drug regimen, have been recognized as crucial elements of high-quality therapy in transitional care. Programs for transitional care may help to reduce medication-related problems, improve access to medication therapy, provide in-depth medication counselling, and fill in medication care gaps following hospital discharge. (Mardani, Griffiths and Vaismoradi, 2020). The nurse chooses which of the patient's primary qualities are crucial for a particular pharmacological therapy. They include things like genetic characteristics, life expectancy, gender, lifestyle, food, and daily routines. Which major interactions between the fundamental patient characteristics and the fundamental drug information will occur is decided by the nurse. The nurse then makes recommendations based on such interactions to improve the therapeutic benefit and decrease adverse effects related to pharmaceutical therapy. The nurse incorporates these strategies into a nursing plan of care. (Maciej Serda et al., 2012). Traditionally, nurses have been in charge of preparing and dispensing medications under the direction of doctors. However, as tasks have shifted from doctors to nurses over the past few decades, nurses' roles have increased. (Maier and Aiken, 2016; De Baetselier et al., 2022). Nurses’ roles have expanded in the past years for more duties than the ordinary ones. This includes pharmacological intervention and medication management. There is a lack of knowledge of these roles and duties.